Studies on the encapsulation of diclofenac in small unilamellar liposomes of soya phosphatidylcholine - Lopes, L. B.; Scarpa, M. V.; Silva, GVJ; Rodrigues, D. C.; Santilli, C. V.; Oliveira, Anselmo Gomes de [UNESP] (Elsevier B.V., 2004)
The encapsulation of acid (AD) and sodium diclofenac (SD) in small unilamellar liposomes (SUV) as well as the interactions of the drug with the bilayer was studied. SUV was prepared by sonication from multilamellar liposomes containing soya phosphatidylcholine and diclofenac at various proportions. The size distribution obtained from dynamic light scattering showed that the incorporation of SD decreases significantly the size of the liposomes suggesting that the drug interacts with the bilayer of the liposomes. This size decrease is related with the phase transition of liposomes to mixed micelar solution. The encapsulation of the hydrophilic dye indocyanine green in the aqueous compartment of liposomes showed that the rate of captured dye decreases with SD concentration suggesting the transition of liposomes to mixed micelles. The P-31 NMR analysis indicates that SD interacts with the phosphate of phosphatidylcholine head groups. A schematic model for interaction of SD with phosphatidylcholine of the liposomes in which the diclofenac anion interacts with the ammonium group of the phospholipid and the dichloropheryl ring occupies a more internal site of bilayer near phosphate group was proposed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: liposome; mixed micelles; phase transformation; light scattering; P-31 NMR